KHI vis-a-vis CLD-KHI: Sejarah atas Dinamika Perdebatan Pelegalan Hukum Islam Indonesia - Asroor, Zaimul; Izzatunnisa, Eva; Ismail, Muhammad (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2023)
The beginning of Indonesia’s independence period was marked by the enthusiasm of the ulama in reformulating Islamic laws after previously Islamic law had been “castrated” by the Dutch. In this paper, the author wants to show the efforts of the Indonesian ulama and government in formulating Islamic law (especially family) to be used as a general benchmark for all Religious Courts in the archipelago. Of course, their efforts to formulate Islamic law are not as easy as turning the palm of their hand, because there are contradictions and differences of opinion. However, the emergence of the 1974 Marriage Law, and then its refinement with the KHI (Compilation of Islamic Law) became a success in itself for the Indonesian government and ulama’ to unite their voices on the issue of Marriage, Endowments and Inheritance. On the other hand, the existence of efforts to renew the KHI through the CLD (Counter Legal Draft)-KHI shows that some groups are dissatisfied with the KHI formulation. However, their efforts were in vain because they were considered to be contrary to Islamic teachings and were finally recorded by the Ministry of Religion.